Sustainable Development Strategy in East Kotawaringin Based Fisheries Sector - Rais, Muhammad (Forum Ilmu Sosial, 2017)
Sampit as the Capital of Kotawaringin Regency has a city mascot in the form of Jelawat Fish Statue. This fish is one of the typical fish species in Borneo and is also a type of 'high caste' fish because it has a fairly competitive economic value. Making the fish as the mascot of the city, of course gives consequences for the area to make fisheries as the leading sector. However, fishery sector has not been developed enough by local government which prioritizes processing industry and trade. While the fishery sector is one of the sectors that provide the dominant contribution to regional income. Therefore it is time for the fishery sector to be developed and improved with various strategies and policies. This is in order to take advantage of space where the territorial waters of Kotim Regency which is quite extensive consists of rivers, lakes, swamps, and beaches should be utilized to the fullest. The choice of aquaculture fishery, because it is considered more efficient and effective both in time and capital. Aquaculture is also more environmentally friendly because it is avoided from the use of trawlers and explosives commonly found in capture fisheries. So this plan meets the value of sustainability as it develops renewable resources, meets ecological, social, and economic and cultural aspects. An ideal development than exploitation activities of time-consuming mining materials, unstable prices, and incapable of empowering communities comprehensively because the processing of mining products in Kotim District is done elsewhere even though the tax revenue for regions is large but unsustainable. while the fisheries sector comprehensively empowers the community from fishermen, fish farmers, industrial-scale entrepreneurs, investors, banks, cooperatives, SME entrepreneurs, and others.